2018
DOI: 10.1007/s10482-018-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

Gallaecimonas mangrovi sp. nov., a novel bacterium isolated from mangrove sediment

Abstract: A Gram-stain negative, rod-shaped, non-motile, strictly aerobic bacterium HK-28 was isolated from a mangrove sediment sample in Haikou city, Hainan Province, China. Strain HK-28 was able to grow at 10-45 °C (optimum 25-30 °C), pH 5.0-8.5 (optimum 6.0-7.0) and 0.5-12.0% (w/v) NaCl (optimum 1.0-3.0%, w/v). The major cellular fatty acids were C, Summed Feature 8 (C ω7c and/or C ω6c), Summed Feature 3 (C ω7c and/or C ω6c), C, C 3-OH and Cω8c. Ubiquinone-8 (Q-8) was the predominant respiratory quinone. The polar li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Isolation efforts inspired by the ichip were also performed using many kinds of sediments, such as marine sediments, mangrove sediment, and estuarine sediment, etc.. These studies have also helped us obtain many unculturable microorganisms, such as Actinomycetota resources and harmful substance degrading bacteria resources [39][40][41]. Generally speaking, this platform has been shown to increase microbial recovery from 5-to 300-fold, depending on the study [19].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation efforts inspired by the ichip were also performed using many kinds of sediments, such as marine sediments, mangrove sediment, and estuarine sediment, etc.. These studies have also helped us obtain many unculturable microorganisms, such as Actinomycetota resources and harmful substance degrading bacteria resources [39][40][41]. Generally speaking, this platform has been shown to increase microbial recovery from 5-to 300-fold, depending on the study [19].…”
Section: Discussionmentioning
confidence: 99%
“…Cells of strains FTZ2 T and FTZ6 T in the late-exponential phase were observed by SEM [39] and TEM [15]. Cell susceptibility to sodium dodecyl sulphate (SDS) was determined by measuring cell growth after injection of anoxic SDS stocks to cultures in mid-logarithmic phase to a final concentration of 0.01 % (w/v) [40].…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%
“…Genome sequencing was performed by the Illumina NovaSeq 6000 PE150 and Oxford Nanopore PromethION 48 platforms (Magigene, Guangdong, PR China). Quality controls of Illumina and Nanopore reads were performed as previously described [15]. Then, clean reads from the Illumina and Nanopore sequencing were assembled with Unicycler (version 0.4.8) with default options [16].…”
Section: Genome and Phylogenymentioning
confidence: 99%
“…This antibiotic was the first new class of antimicrobials found after 30 years, representing a promising alternative chemotherapeutic agent to control infections caused by multidrug-resistant bacteria. Other studies have shown the applicability of iChip-like devices to culture microbes from aquatic environments and organisms, such as from mangroves ( 105 ) and sponges ( 37 ).…”
Section: Accessing the Cultured Coral Microbiomementioning
confidence: 99%